Host association influences variation at salivary protein genes in the bat ectoparasite Cimex adjunctus. (11th April 2018) - Talbot, Benoit; Vonhof, Maarten J.; Broders, Hugh G.; Fenton, Brock; Keyghobadi, Nusha
Abstract: Parasite–host relationships create strong selection pressures that can lead to adaptation and increasing specialization of parasites to their hosts. Even in relatively loose host–parasite relationships, such as between generalist ectoparasites and their hosts, we may observe some degree of specialization of parasite populations to one of the multiple potential hosts. Salivary proteins are used by blood‐feeding ectoparasites to prevent hemostasis in the host and maximize energy intake. We investigated the influence of association with specific host species on allele frequencies of salivary protein genes in Cimex adjunctus, a generalist blood‐feeding ectoparasite of bats in North America. We analysed two salivary protein genes: an apyrase, which hydrolyses ATP at the feeding site and thus inhibits platelet aggregation, and a nitrophorin, which brings nitrous oxide to the feeding site, inhibiting platelet aggregation and vasoconstriction. We observed more variation at both salivary protein genes among parasite populations associated with different host species than among populations from different spatial locations associated with the same host species. The variation in salivary protein genes among populations on different host species was also greater than expected under a neutral scenario of genetic drift and gene flow. Finally, host species was an important predictor of allelic divergence in genotypes of individual C. adjunctus at both salivary protein genes. Our results suggest differing selection pressures on these two salivary protein genes in C. adjunctus depending on the host species.